Challenges of Human Resource Management in Facing Technological Developments (Case Study at the Alfarezi Store, Kamal District) - Tia Astaivada; Helmi Zulkarnain; Hestina Indriyani Putri; Iriani Ismail (PT FORMOSA CENDEKIA GLOBAL, 2023)
The aim of writing this article is to discuss HRM challenges in facing technological developments in the form of payments via E-Wallet and the use of cash registers. The method used in this article is qualitative, with data collection techniques through observation, literature study and interviews. And using descriptive analysis techniques using primary and secondary data. The results of this research show that the digital era has had a major impact on the world of work, including the increasing need for HR competency. It is important for business owners to be aware of technological developments, and business owners need to follow the flow of technological developments. The challenges in facing the digital era are not only related to technological competence, but also involve human aspects and soft skills such as work ethics, social sensitivity and employee adaptability. Collaboration between business owners and employees is also required